The electrical properties of isolated microtubules - Brenda C. Gutierrez; Horacio F. Cantiello; María del Rocío Cantero (Scientific Reports, 2023)
Abstract This study examines the electrical properties of isolated brain microtubules (MTs), which are long hollow cylinders assembled from αβ-tubulin dimers that form cytoskeletal structures engaged in several functions. MTs are implicated in sensory functions in cilia and flagella and cellular activities that range from cell motility, vesicular traffic, and neuronal processes to cell division in the centrosomes and centrioles. We determined the electrical properties of the MTs with the loose patch clamp technique in either the presence or absence of the MT stabilizer Paclitaxel. We observed electrical oscillations at different holding potentials that responded accordingly in amplitude and polarity. At zero mV in symmetrical ionic conditions, a single MT radiated an electrical power of 10–17 W. The spectral analysis of the time records disclosed a single fundamental peak at 39 Hz in the Paclitaxel-stabilized MTs. However, a richer oscillatory response and two mean conductances were observed in the non-Paclitaxel MTs. The findings evidence that the brain MTs are electrical oscillators that behave as "ionic-based" transistors to generate, propagate, and amplify electrical signals.